DEVELOPMENT OF INTERACTIVE MULTIMEDIA-BASED GYMNASTICS FLOOR TECHNIQUES LEARNING MODEL FOR JUNIOR HIGH SCHOOL STUDENTS - Ari Wibowo Kurniawan; James Tangkudung (Program Pascasarjana Universitas Negeri Jakarta, 2017)
Based on preliminary observations conducted on teachers and students of SMP Negeri in Malang Regency: (1) students can not and do not like the material gymnastics floor, and tend to like the material of big ball game (92%); (2) students state that educators have never done teaching with media in the form of interactive multimedia, 100%; and (3) students agree when done an development of interactive multimedia media for learning basic technique of gymnastic floor 100%. The purpose of this research and development is to develop an effective model of basic techniques of floor gymnastics for junior high school students using interactive multimedia. In this study is using development research methods from Borg and Gall (1983: 775), and researchers did not use the whole but only using 7 steps. The 7 steps chosen by the researchers are as follows: (1) collecting information, (2) initial product design, (3) expert evaluation, (4) trial in phase I , (5) product revision (6) trials in phase II, (7) revisions and final products. Based on the result of data analysis of the evaluation of the learning expert is very valid, the evaluation of expert gymnastics is very valid, the evaluation of media expert is very valid. From the data analysis result of small group trial is valid enough (73,1% ), while large group trial is very valid (85,75%), thus it can be concluded that the development of interactive multimedia-based floor gymnastic basic technique for junior high school student can be used.. Keywords: Development, learning, gymnastics floor, interactive multimedia